2018
DOI: 10.12973/eu-jer.7.3.601
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Preschool Teachers’ Academic Achievements Depending on Their Goal Orientations, Critical Thinking Dispositions and Self-Regulation Skills

Abstract: The aim of this study is to explain and predict prospective preschool teachers' academic achievements depending on goal orientations they adopt, their critical thinking dispositions and self -regulation skills. Research sample constitutes of 265 prospective preschool teachers attending the Faculty of Educational Sciences in Cukurova University. Research data were collected with th e 2x2Achievement Goal Orientations Scale, Self-Regulation Questionnaire and Critical Thinking Disposition Scale. Demographical info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…The lack of research on the role of metacognition in physics problem solving is a problem, considering the importance of problem-solving in improving physics learning achievement (Chi, 2006;Yuberti et al, 2019). Practitioner-oriented studies have investigated the correlation between awareness and metacognitive achievement (Sart, 2014), with some studies showing evidence that the students who managed their cognition tend to work better in problem-based learning (Hmelo-Silver, 2004;Uyar, Yilmaz Genc, & Yasar, 2018), and in improving academic achievement (Winston, Van Der Vleuten, & Scherpbier, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The lack of research on the role of metacognition in physics problem solving is a problem, considering the importance of problem-solving in improving physics learning achievement (Chi, 2006;Yuberti et al, 2019). Practitioner-oriented studies have investigated the correlation between awareness and metacognitive achievement (Sart, 2014), with some studies showing evidence that the students who managed their cognition tend to work better in problem-based learning (Hmelo-Silver, 2004;Uyar, Yilmaz Genc, & Yasar, 2018), and in improving academic achievement (Winston, Van Der Vleuten, & Scherpbier, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Given that, students who adopt MGs have higher level of grit compared to PAGs. As suggested by Uyar et al (2018), this resulted in better academic achievement. They revealed that students who adopted more learning approach (i.e., MGs) were more likely to be classified among the high achieving students.…”
Section: Discussionmentioning
confidence: 77%
“…Other research has revealed that MGs positively influence enjoyment and negatively relate to anxiety and boredom throughout the academic year (Ranellucci, Hall, & Goetz, 2015). A recently published study supported the association between the MGs and the academic achievement (Uyar, Genc, & Yasar, 2018). They found that high achieving students adopted a more learning approach (i.e., MGs) relative to those with medium and low level of academic achievement.…”
Section: Achievement Goal Orientations (Agos)mentioning
confidence: 91%
“…Others have documented this phenomenon that a greater interest in the material by the teacher may lead to children having a greater interest in the material (Brener et al, 2013;Lavin, 1993). It also has been documented that teachers with greater job satisfaction (Dinc & Kocyigit, 2017) and greater academic achievement (Uyar et al, 2018) have a greater commitment to teaching. Although, job satisfaction was not evaluated in the iGrow readers FOI, the instructional component of FOI was measured.…”
Section: Discussionmentioning
confidence: 98%